Body Stalk Anomaly in a 24-Week Singleton Pregnancy: Prenatal Sonographic Diagnosis and Differentiation from OEIS Complex and Pentalogy of Cantrell - A Case Report - Edvans Henry; Abarham Martadiansyah; Nuswil Bernolian (Lembaga Publikasi Ilmiah Nusantara, 2026)
Body stalk anomaly (BSA), also known as the limb–body wall complex, is a rare and almost uniformly lethal fetal malformation characterized by a large anterior abdominal wall defect with visceral herniation, severe kyphoscoliosis, and an absent or markedly short umbilical cord. We report a 19-year-old woman, gravida 1, referred at 17–18 weeks with a presumptive diagnosis of gastroschisis and diaphragmatic hernia. Serial transabdominal ultrasonography at our maternal–fetal medicine unit demonstrated a wide anterior abdominal wall defect with total herniation of the liver, stomach, and bowel into a covering membrane, oligohydramnios at 20 weeks, scoliosis, and a short umbilical cord with the fetal trunk lying close to the placenta. These findings fulfilled the Van Allen diagnostic criteria for BSA and allowed differentiation from OEIS complex and pentalogy of Cantrell. The fetal karyotype was clinically presumed normal, and maternal serology was non-contributory. Given the lethal nature of the condition, the family received detailed counseling regarding the grave fetal prognosis, recurrence risk, and management options, including elective termination at a tertiary center. This report underscores the central role of systematic second-trimester sonography in diagnosing BSA, distinguishing it from other anterior abdominal wall defects with more favorable outcomes, and guiding parental counseling.